Measuring Information System-Based Village Administration Service Performance Using Boundary Value Analysis Techniques - Dodik Arwin; DYAHAYU WULAN; Hafiz Rizqon Adinata (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Application development often does not have a significant impact on users, especially various application functions that make it difficult for users to take advantage of the system optimally. System testing plays an important role in an application development. Tests are carried out to ensure that all programs run properly before an application is released. This study discusses the measurement of performance on the administration service website application with the Black Box Testing method. Functional testing is carried out using the Boundary Value Analysis technique. Boundary Value Analysis technique is one of the techniques of Black Box testing that identifies errors from the outside or inside of a system. With this technique, the success of an input data value is tested based on the upper and lower limit values. The result of the measurement of the administrative service application is the optimal system functionality and in accordance with the user's business process needs. The percentage of success rate for fields on the Register Account menu is 91.67% and Login is 75%. Meanwhile, on the Daftar Surat Izin Keramaian menu, it has a success rate of 80%.